Bibliophobia : a memoir - Chihaya, Sarah (Random House, 2025)
"Have you ever read a book and felt so gutted by it that you knew you'd never recover? That it made you sit differently in your own skin? A book that complicated everything you believed in and changed the way you read the world around you forever? This is what Sarah Chihaya calls a "Life Ruiner". Sarah's Life Ruiner was The Bluest Eye by Toni Morrison. When she read it in her high school English class, she could no longer pretend not to notice how alien she felt as a Japanese American in a predominantly White suburb of Cleveland. Shaken, she set out on a quest-for the book that would show her who she was and how to live in an inhospitable world. There were lots of scripts available, and she tried to follow them-skinny athlete, angsty artist, ambitious academic. But a lifelong struggle with depression thwarted the resolution to every plot, and when she was hospitalized for a nervous breakdown, the world became an unreadable blank page. In the aftermath, she was faced with a question: can we ever truly rewrite the stories that govern our lives? Alternately searing and laugh-out-loud funny, Bibliophobia is a deft combination of memoir and criticism in the vein of Geoff Dyer and Olivia Laing. Through a series of books, including The Bluest Eye, Anne of Green Gables, Possession, A Tale for the Time Being, and The Last Samurai, Sarah Chihaya interrogates her cultural identity, her relationship with depression, and the necessary and painful ways that books can push back on the readers who love them"--